Junior female ice hockey players' social and psychological needs within their motivational domains - Gaifullina, N. G.; Makarova, O. A.; Ljdokova, G. M. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to analyze motivational agendas of junior (7-10 year-old) female ice hockey players (n=20) with the influences and contributions of their family members (n=20). The players` socio-psychological needs were studied within their motivational domains using the relevant questionnaire survey and test methods. Motivational domains of this age group are often currently determined by a variety of external influences. The players` families more often than not appreciate the growing prestige and popularity of the modern ice hockey in the first place and consider the actual needs and expectations of their children in the second place. In the hierarchy of family expectations, the daughters are generally viewed as the highly ambitious personalities reputable in their peer subcultures and respected by adults. A questionnaire survey data and analysis showed the female players being well socially adapted to both school and ice hockey team environments. They report feeling comfortable at their classes, often praised by class teachers, pleased by the team spirit in their ice hockey teams and competitive successes and having good support from the coaches. In their peer contacts, the female ice hockey players prefer playing with the same-sex children and tested to psychologically progress within the feminine type. The study found certain matches of a variety of socio-psychological needs in the children and their families including the last for success; need for approval from respected adults and peers; and the need for their uniqueness to be recognized. Therefore, the study data were found to run counter to our prior assumption that the junior female ice hockey players might be in need of their `manliness` being offset by the relevant socio-psychological accommodation factors as they face a variety of social problems in contacts with the same-sex peers and adults due to their higher demand for physical activity.